Effects of phosalone plant pesticide on sperm parameters and sexual hormone levels in Wistar rats: An experimental study - Fahime Mazaheri; Kazem Kamali Aliabad; Seyed Mehdi Kalantar; Noosha Ziya; Arezoo Khoradmehr; Morteza Anvari (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Phosalone is an organophosphate insecticide, applied to control of plant pests. This compound has various side effects because it acts as an acetyl cholinesterase enzyme inhibitor. Objective: To investigate the effects of phosalone on the sperm parameters of and levels of sex hormones in adult male rats. Materials and Methods: In this experimental study, 16 adult (8-12 wk) male Wister rates (weighing 220-280 gr) were randomly assigned into 4 groups (n = 4/each). Group 1 (control) received only routine adequate water and food; Group 2, 3, and 4 received different low doses of phosalone (60, 90, and 120 mg/kg respectively). The rats were weighed and anesthetized after 48 days. Sperm parameters including number, motility, and viability as well as sex hormones (such as Luteinizing Hormone, Follicle Stimulating Hormone, and testosterone) were evaluated and compared after removing the epididymis tail. Results: Our results showed that phosalone decreased sperm motility, viability, and number in a dose-dependent manner. The level of FSH and LH was increased, and testosterone was decreased. Also, depending on the dose, phosalone decrease sperm motility and viability (p ≤ 0.001), while the level of FSH and LH was increased and testosterone was decreased (p = 0.861). Conclusion: Phosalone has negative effects on reproductive indices in male rats and can cause serious damage and decrease the number and sperms motility. It can also cause infertility due to changing the concentration of hormones.Key words: Organophosphate, Pesticides, Phosalone, Sperm, Sex hormones.}